2021
DOI: 10.3390/s21041349
|View full text |Cite
|
Sign up to set email alerts
|

Coal and Gangue Separating Robot System Based on Computer Vision

Abstract: In coal production, the raw coal contains a large amount of gangue, which affects the quality of coal and pollutes the environment. Separating coal and gangue can improve coal quality, save energy, and reduce consumption and make rational use of resources. The separated gangue can also be reused. Robots with computer vision technology have become current research hotspots due to simple equipment, are efficient, and create no pollution to the environment. However, the difficulty in identifying coal and gangue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Not only could it achieve the precise identification of the gangue, but it also obtained information about the relevant locations of the gangue, which could be applied to the target detection task of the gangue. Sun et al [17] studied the classification and location of coal and gangue, proposed a dynamic object detection approach in view of CG-YOLO, and used robots to grab irregularly shaped gangue to form a complete separation system. Luo et al [18] improved the backbone and neck of YOLOv5, implemented a deep lightweight target inspection network, and ensured speed and precision in detecting multiple types of materials on belt conveyors.…”
Section: Introductionmentioning
confidence: 99%
“…Not only could it achieve the precise identification of the gangue, but it also obtained information about the relevant locations of the gangue, which could be applied to the target detection task of the gangue. Sun et al [17] studied the classification and location of coal and gangue, proposed a dynamic object detection approach in view of CG-YOLO, and used robots to grab irregularly shaped gangue to form a complete separation system. Luo et al [18] improved the backbone and neck of YOLOv5, implemented a deep lightweight target inspection network, and ensured speed and precision in detecting multiple types of materials on belt conveyors.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-based image recognition technology is used to reflect raw coal on the conveyor belt with γ and X rays. γ and X-rays can be identified by different degrees of radiation absorption or attenuation in coal and gangue (Zhang and Liu 2018;Robben et al 2020), but this kind of equipment is radioactive (Sun et al 2021). CCD industrial cameras use no radiation and low cost, so they are widely used.…”
Section: Introductionmentioning
confidence: 99%
“…However, γ-ray is not widely used because of its strong radiation and high price [12]. The visible light-based machine vision technology [13] has no radiation, high efficiency, and low cost, and is widely applied to the field of coal and gangue identification. Based on machine vision technology, Li et al found that the four features of gray variance, skewness, texture contrast, and entropy have the strongest separability through the analysis of the grayscale and texture information of coal gangue [14].…”
Section: Introductionmentioning
confidence: 99%